Microstrip Rectangular Patch Array Antenna for Tsunami Radar - Fitrilina Fitrilina; Junas Haidi; Alex Surapati; Hendy Santosa; Firdaus; Rudy Fernandez (JURNAL NASIONAL TEKNIK ELEKTRO, 2022)
Tsunami radar is one of the detection tools used in the tsunami early warning system. The most commonly used is high-frequency radar with a long-range but high power and low resolution. However, in order to improve the reliability of the tsunami warning system in detecting signs of a tsunami and monitoring with a high speed of updating information, a radar system with a high resolution is needed. High resolution can only be obtained by a radar that has a large bandwidth in the radio spectrum. Increasing the bandwidth can be done by increasing radar operating frequency. An antenna is one of the essential components that can determine the performance of the radar system. Therefore, in this study, an antenna was designed at Super High Frequency to be applied to a radar system. The designed antenna is a microstrip antenna with a rectangular patch using array method. The desired specifications at a frequency of 5.8 GHz are return loss ≤-10 dB, VSWR ≤2, bandwidth >150 Mhz, beamwidth >200. After the simulated design met the specifications, the fabrication and measurements were later carried out. The measurement results show a frequency shift to 5,71 GHz with a return loss of -21,346, VSWR of 1,186, bandwidth of 200 MHz, a beamwidth of 40o and gain 11.65 dB. Thus, the proposed antenna, the 8-rectangular patch microstrip array antenna, can be applied in tsunami radar systems.